The Potential Interplay of Adipokines with Toll-Like Receptors in the Development of Hepatocellular Carcinoma. (25th September 2011) - Wang, Shen-Nien; Wang, Sen-Te; Lee, King Teh
Abstract : Toll-like receptors (TLRs) are not only crucial to the initiation of the immune system, but also play a key role in several human inflammatory diseases. Hepatocellular carcinoma (HCC) is among those human cancers, which arise from sites of chronic inflammation. Therefore, a number of studies have explored the potential contribution of TLRs to HCC occurrence, which is initiated by exposure to chronic hepatic inflammation of different etiologies (including ethanol, and chronic B and C viral infections). Recent epidemiological data have shown the association of obesity and HCC development. Given the fact that adipose tissues can produce a variety of inflammation-related adipokines, obesity has been characterized as a state of chronic inflammation. Adipokines are therefore considered as important mediators linking inflammation to several metabolic diseases, including cancers. More recently, many experts have also shown the bridging role of TLRs between inflammation and metabolism. Hopefully, to retrieve the potential interaction between TLRs and adipokines in carcinogenesis of HCC will shed a new light on the therapeutic alternative for HCC. In this paper, the authors first review the respective roles of TLRs and adipokines, discuss their mutual interaction in chronic inflammation, and finally anticipate further investigations of this interaction in HCC development.